Pelatihan Pengembangan Video Berbasis Artificial Intelligence Pembelajaran di MAN 1 Majene - Hakim, Abdul; Sinaga, Andromeda Valention; Aswan, Dedy; Malik, Agung Rinaldy; Marsa, Ivan Fachrul (Paramacitra Jurnal Pengabdian Masyarakat, 2024)
Community Service Program aims to improve the quality of learning at MA Negeri 1 Majene through training in the development of AI-based learning videos. With the help of AI technology, teachers are trained to create more interactive and engaging video content to enhance students' understanding and motivation to learn. The training activities are conducted through a series of sessions that cover basic theory, hands-on video creation, and the use of AI-based applications. The results of this training show that teachers have successfully mastered the basic skills of designing and editing AI-based videos, which can then be applied in the classroom to support the learning process. This program is expected to have a long-term impact on the quality of teaching at MA Negeri 1 Majene by providing more dynamic and relevant learning media for students.